A new spider genus (Araneae: Linyphiidae: Erigoninae) from a tropical montane cloud forest of Mexico - Ibarra-Núñez, Guillermo; Chamé-Vázquez, David; Maya-Morales, Julieta (European Journal of Taxonomy, 2021)
A new genus and species of spider (Araneae, Linyphiidae, Erigoninae) from a tropical montane cloud forest of Mexico is described from both male and female specimens, Xim trenzado gen. et sp. nov. A phylogenetic parsimony analysis situates Xim gen. nov. as a distinct genus among the distal Erigoninae. Xim gen. nov. is sister to a clade including Ceratinopsis, Tutaibo and Sphecozone, but differs from those genera by having a high cymbium, large paracymbium, short straight embolus, male cheliceral stridulatory striae widely and evenly spaced, both sexes with a post-ocular lobe, male with two series of prolateral macrosetae on femur I, and the female by having strongly oblong, u-shaped spermathecae.